Exigências indispensáveis para ser discípulo de Jesus um estudo exegético-teológico de Lc 14,25-33 - Nascimento Junior, Maurino Marques (2017)
The gospel according to Luke, in the extended section of Jesus' ascent to Jerusalem (Lk 9:51–19:28), presents the conditions cited by Jesus for one to become his disciple. The purpose of this dissertation is to examine each of these conditions by focusing specifically on the text of Luke 14:25-33. To do so, an exegetical analysis of the text will be developed, which will serve as a basis for a subsequent theological analysis and consequent hermeneutic actualization. The theme is relevant, since discipleship has been and remains the essence of the Christian life in the sense of a godly life in community. The methodology applied in this work will be guided by a bibliographical research, which will be based on several authors, who have developed studies and research on the subject. The conditions put forward by Jesus, presented in the Lucan text, express the radicality and the necessity of a conscious decision on the position that will be adopted before them. From these factors will depend a genuine position as a disciple of Jesus Christ, who obeys and follows